Community Empowerment in the Management of Coastal Areas and Small Islands to Achieve the Welfare of Local Communities - Dilla Hariyanti; Mugiati Mugiati; Badrunsyah Badrunsyah (Publikasi Indonesia, 2024)
So far, government policy which is more land-oriented and exploiting the potential of coastal areas and small islands is still not optimal. People's prosperity is the ideal of the Indonesian nation in realizing social (social) welfare, for this reason it is necessary for the government to play a role in realizing or meeting the needs of coastal communities and small islands to get a decent living and realize people's welfare, the government can carry out land and ecosystem management. in it by empowering local communities based on their potential and characteristics, as well as analyzing community needs by considering social, economic, cultural and environmental conditions. The regional government encourages community business activities in managing coastal areas and small islands (PWP-3-K) and provides guidance through guidance, legal assistance, outreach, education, training and counseling.